Florida Solid and Hazardous Waste Regulation Handbook: Contact Agencies - Michael T. Olexa; Aaron Leviten; Kelly Samek (EDIS)
This is EDIS document FE468, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.